Social representations of users over 50 years about the internet and online social networks (Research, Society and Development, 2022)
This study aimed to know the social representations of people aged 50 or over about the internet and online social networks. 50 people participated, with an average age of 60 years, ranging between 50 and 82 years. Participants answered a sociodemographic questionnaire and the Free Word Association Technique (TALP), having as stimuli: “Internet” and “online social networks”. Using the Iramuteq software, multiple frequency analysis, similarity analysis, as well as prototypical analysis were performed. The results show that the participants' social representations about the internet refer to a means of communication, which helps in the search for information and in the provision of virtual social networks. On the stimulus online social networks, social representations were observed as a source of updating, in addition to being another means of communication. In general, the internet and online social networks are seen by participants as both good and bad simultaneously, demanding care from users.